2020
DOI: 10.1007/s00383-020-04760-7
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with universal preoperative and pre-procedural screening for COVID-19 in low-risk pediatric surgical patients requiring general anesthesia

Abstract: Purpose The COVID-19 pandemic has placed extraordinary demands on healthcare services worldwide. Some have reported increased viral transmission to healthcare workers during aerosol-generating procedures such as intubation. We report our experience with universal preoperative and preprocedural screening for COVID-19 in children requiring general anaesthesia with low risk of having the infection. Methods This was a data review involving children aged < 18 years undergoing procedures under general anaesthesia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In another large multicenter study in the States, there were 0.58% positive preoperative screening tests among 1198 patients undergoing orthopedic surgery [ 14 ]. Another preoperative screening study in Malaysia reported no positive screening tests in low-risk asymptomatic patients [ 15 ]. The study of preoperative CT chest in the UK reported 7% of patients with positive COVID-19 related lung change, but only 1.6% had confirmed COVID-19 by RT-PCR [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another large multicenter study in the States, there were 0.58% positive preoperative screening tests among 1198 patients undergoing orthopedic surgery [ 14 ]. Another preoperative screening study in Malaysia reported no positive screening tests in low-risk asymptomatic patients [ 15 ]. The study of preoperative CT chest in the UK reported 7% of patients with positive COVID-19 related lung change, but only 1.6% had confirmed COVID-19 by RT-PCR [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the high incidence of household transmission, 16‐18 prompted us to test both patient and caregiver to lower the possibility of false‐negative results that could lead to intrahospital transmission of the virus. This approach is considered a higher level of attention posed to the risk of viral transmission and has not been proposed elsewhere 19‐21 ; it proved effective at least in 1 case of the 7 positive (14% of total number of positive results). Strength of this study resides, in our opinion, in the strength of this approach to the child‐caregiver unity.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the variable incubation period of COVID-19, ranging up to 14 days, we believe this design gave us the optimal opportunity to detect any cases of symptomatic COVID-19 or respiratory complications that may have presented after hospital discharge. The only study to our knowledge to include formal 14-days follow up of patients was that by Sii et al In a much smaller cohort of 66 patients undergoing elective surgery with negative preoperative test, the authors reported no case of COVID-19 at 14-day follow-up [ 17 ].…”
Section: Discussionmentioning
confidence: 99%